Hume family papers - Hume, George, 1697-1760.
Correspondence and other documents of the Hume family pertaining to family genealogy (1810-1902); and a notebook (1755) of George Hume, surveyor of Frederick County, Va.
Collection material in English.
Keywords: Hume family; Surveying -- Virginia -- Frederick County